Impact of COVID on management of urological cases in a tertiary care non-COVID institute: A patient-centered study - Vipin Chandra; Vishrut Bharti; Rajesh Tiwari; Vijoy Kumar; Ahsan Ahmad; Rohit Upadhyay; Khalid Mahmood; Nikhil Ranjan (Wolters Kluwer -Medknow Publications, 2022)
Background: Health-care systems across the globe have been overwhelmed by coronavirus disease-19 (COVID 19). It has affected non-COVID patient management as well. While service, hospital-oriented data on effect of the pandemic on urological diseases have been published, there is scarce data on patient-centered issues in urology, particularly from India. Hence, we planned this study to determine the impact of COVID on management of urological cases. Materials and Methods: This is a prospective observational single-center study conducted at Indira Gandhi Institute of Medical Sciences, Patna, from April 2020 to November 2020. Consecutive non-COVID adult patients presenting to the indoor, outdoor, and telemedicine services of the urology department of our institute were included. Patients who were moribund, having altered sensorium, severe cardiorespiratory illness, unable to understand and respond, and those unwilling to participate were excluded from the study. A questionnaire-based data were collected. The same interviewer explained the questionnaire to patients in their own language (English/Hindi/Bhojpuri) either in person or telephonically and recorded the findings. Results: Two hundred consecutive patients were screened. One hundred and fifty were included in the study. Mean age of patients was 50 ± 3.2 years. One hundred and five patients were male. Thirty-eight patients had comorbid conditions. One hundred and thirty-seven patients reported delay to consult an urologist since development of the first urological symptom. The average delay was 68 ± 20 days. Thirty-two patients suffered COVID-19 disease during the urological illness. One hundred and twelve were advised for urology consultation after the first evaluation at a local health-care center. The reasons cited for delay by these patients (n = 112) were lock-down and reduced/unavailable public transport (n = 20) and fear of contacting corona infection (n = 10), both (n = 56), suffered COVID-19 (n = 18), and others (n = 8). The distance of patients' residence from the hospital was median 50 km, with interquartile range of 5-254 km. One hundred and three patients received definitive treatment and 47 were still undergoing delays due to various reasons. Sixty-two patients were advised surgery. 25 of these 62 were found to have complications due to delay. Conclusion: Delay in all aspects of management of urological illness, including consultation, work up, and definitive treatment was observed. Of all who were advised surgery, about 40% were found to have complications due to delay in surgery.